Aortic valve disease in diabetes: Molecular mechanisms and novel therapies. Issue 20 (24th September 2021) - Manduteanu, Ileana; Simionescu, Dan; Simionescu, Agneta; Simionescu, Maya
Abstract: Valve disease and particularly calcific aortic valve disease (CAVD) and diabetes (DM) are progressive diseases constituting a global health burden for all aging societies ( Progress in Cardiovascular Diseases . 2014;56(6):565: Circulation Research . 2021;128(9):1344). Compared to non‐diabetic individuals ( The Lancet . 2008;371(9626):1800: The American Journal of Cardiology . 1983;51(3):403: Journal of the American College of Cardiology . 2017;69(12):1523), the diabetic patients have a significantly greater propensity for cardiovascular disorders and faster degeneration of implanted bioprosthetic aortic valves. Previously, using an original experimental model, the diabetic‐hyperlipemic hamsters, we have shown that the earliest alterations induced by these conditions occur at the level of the aortic valves and, with time these changes lead to calcifications and CAVD. However, there are no pharmacological treatments available to reverse or retard the progression of aortic valve disease in diabetes, despite the significant advances in the field. Therefore, it is critical to uncover the mechanisms of valve disease progression, find biomarkers for diagnosis and new targets for therapies. This review aims at presenting an update on the basic research in CAVD in the context of diabetes. We provide an insight into the accumulated data including our results on diabetes‐induced progressive cell and molecular alterations in the aortic valve, new potential biomarkers to assess the evolution and therapy of the disease, advancement in targeted nanotherapies, tissue engineering and the potential use of circulating endothelial progenitor cells in CAVD.